1984
DOI: 10.1002/tea.3660210410
|View full text |Cite
|
Sign up to set email alerts
|

Toward the development of a children's science curiosity measure

Abstract: Based on the need for, suggestions about the construction, and existing measures serving as models found in the literature both inside and outside of science education, the “Children's Science Curiosity Scale” has undergone six versions using four different samples of fifth graders. Respectable internal consistency (alpha) and test‐retest reliabilities have been calculated. Concurrent validity has been demonstrated by significant positive correlations with another recognized curiosity measure, and by way of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
1
45
0
2
Order By: Relevance
“…The test was administered in accordance with the manual at times when the children were interviewed. Science curiosity was measured using a technique developed for American fifth graders (Harty & Beall, 1984; see also Gardner, 1987). In essence, the Harty -Beall measure of science curiosity is derived from a 30-statement questionnaire to which children respond using a Likert-type scale.…”
Section: Location and Participantsmentioning
confidence: 99%
“…The test was administered in accordance with the manual at times when the children were interviewed. Science curiosity was measured using a technique developed for American fifth graders (Harty & Beall, 1984; see also Gardner, 1987). In essence, the Harty -Beall measure of science curiosity is derived from a 30-statement questionnaire to which children respond using a Likert-type scale.…”
Section: Location and Participantsmentioning
confidence: 99%
“…Curiosity has often been highlighted as an important attribute and influencing factor with respect to students' learning (Borowske, 2005). Literature studies showed that higher curious students probably achieve better than lower curious students (Harty & Beall, 1984) because of their exploration of events and objects for longer periods time and their use of many more senses. Curious youngsters will recall experiences longer, comprehend better and achieve a more complete learning (Harty & Beall, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been little research presented concerning the effects of school ground lessons on scientific curiosity. Internal inspiration that drives students to know more about science as what Harty and Beall (1984) defined as scientific curiosity is affected by the factors of novelty, lack of clarity, complexity of stimuli and surprise or bafflement. Unfortunately these factors have little been researched among primary school students in school ground lessons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cohen, Manion, and Morrison 2000). To the uninitiated, this is perhaps the driest and most off-putting yet essential aspect of learning styles research (see Harty and Beall 1984, 1987and Gardner 1987 for a good example of argument and counter-argument associated with the development of a children's attitude measure). Establishing face validity (that the instrument actually measures what it reports to measure, literally taken at face value), construct validity (that any measurement produced by the instrument is fairly explained by appropriate learning styles constructs or concepts), predictive validity (that any measurement produced by the instrument …”
Section: Validity and Reliabilitymentioning
confidence: 99%